DECISION MAKING MARKET EXPANSION STRATEGY WITH CASE STUDY: JAMBAN START-UP IN INDONESIA USING ANALYTICAL HIERARCHY PROCESS (AHP) - Satriyo Utomo, Jenjang
PT. Jawara Bersih Nusantara (known as the "Jamban" brand name) is a leading startup company in the sanitation business, especially public toilets in Indonesia. The business was set up by a number of sanitation observers in Indonesia at the end of 2019. Jamban strives to provide service product solutions to facilitate customer access to Indonesia's best sanitation, especially in tourist attractions and public places in Indonesia. In solving this problem, the management must determine a new location for Jamban in Indonesia. City selection will be necessary for Jamban at an early stage because each city has a different potential to be entered. Due to the limited available resources, Jamban Management must choose the most promising future expansion in terms of business and benefits. This study aims to set up the decision-making model to choose a suitable new venue. Jamban management has various considerations to determine the selection process. Also, there are several criteria for review in the decision-making process. The analysis used the Analytical Hierarchy Process (AHP) method to compile a systematic hierarchy problem using this method. All data were obtained using qualitative and quantitative methods through interviews and questionnaires. This AHP model integrates objective and subjective inputs by decision-makers, formulated into a scientific model to develop main criteria and sub-criteria, so a weighted score normalization is produced. The stakeholder was asked to perform an assessment process with a pairwise comparison from every main criterion, sub-criterion, and all alternative. The researcher used the AHP calculation formula based on Microsoft Excel developed by Klaus D Goepel during the data processing. As the results of a series of AHP procedures were carried out in this report, It can be concluded that this type of AHP is very useful in supporting the decision-making process for the selection of Jamban business locations and the recommended site for the Jamban branch, Indonesia.